2020
DOI: 10.1002/cne.25050
|View full text |Cite
|
Sign up to set email alerts
|

Corticocuneate projections are altered after spinal cord dorsal column lesions in New World monkeys

Abstract: Recovery of responses to cutaneous stimuli in the area 3b hand cortex of monkeys after dorsal column lesions (DCLs) in the cervical spinal cord relies on neural rewiring in the cuneate nucleus (Cu) over time. To examine whether the corticocuneate projections are modified during recoveries after the DCL, we injected cholera toxin subunit B into the hand representation in Cu to label the cortical neurons after various recovery times, and related results to the recovery of neural responses in the affected area 3b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 113 publications
(225 reference statements)
0
6
0
Order By: Relevance
“…Research in non-human primate models of chronic and complete cervical SCI has shown that the S1 hand area becomes largely unresponsive to tactile hand stimulation after the injury (Jain et al, 2008;Kambi et al, 2014;Liao et al, 2021). The surviving fingerrelated activity became disorganised such that a few somatotopically appropriate sites but also other somatotopically nonmatched sites were activated (Liao et al, 2021). Seminal nonhuman primate research has further demonstrated that SCI leads to extensive cortical reorganisation in S1, such that tactile stimulation of cortically adjacent body parts (e.g., of the face) activated the deprived brain territory (e.g., of the hand; Halder et al, 2018;Jain et al, 2008;Kambi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in non-human primate models of chronic and complete cervical SCI has shown that the S1 hand area becomes largely unresponsive to tactile hand stimulation after the injury (Jain et al, 2008;Kambi et al, 2014;Liao et al, 2021). The surviving fingerrelated activity became disorganised such that a few somatotopically appropriate sites but also other somatotopically nonmatched sites were activated (Liao et al, 2021). Seminal nonhuman primate research has further demonstrated that SCI leads to extensive cortical reorganisation in S1, such that tactile stimulation of cortically adjacent body parts (e.g., of the face) activated the deprived brain territory (e.g., of the hand; Halder et al, 2018;Jain et al, 2008;Kambi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research in non-human primate models of chronic and complete cervical SCI has shown that the S1 hand area becomes largely unresponsive to tactile hand stimulation after the injury ( Jain et al, 2008 ; Kambi et al, 2014 ; Liao et al, 2021 ). The surviving finger-related activity became disorganised such that a few somatotopically appropriate sites but also other somatotopically non-matched sites were activated ( Liao et al, 2021 ). Seminal non-human primate research has further demonstrated that SCI leads to extensive cortical reorganisation in S1, such that tactile stimulation of cortically adjacent body parts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated how the somatosensory system undergoes functional recovery after sensory loss by unmasking or forming new connections ( 15 , 19 , 31 37 ; see ref. 26 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed microelectrode maps of the large representation of hand and arm in the primary somatosensory cortex (3b) revealed the changes in somatotopy most clearly. Descending inputs from the sensorimotor cortex to the Cu ( 19 ), along with the remaining second-order dorsal column afferents, may facilitate the reactivation although their roles are mainly modulatory ( 20 ).…”
mentioning
confidence: 99%
“…Other series were processed stains for Nissl, cytochrome oxidase (CO; Wong‐Riley, 1979), vesicular glutamate transporter 2 (VGLUT2), or parvalbumin (PV) that revealed the architectonic features of brain structures. See details in previous publications (Liao et al., 2021; Turner et al., 2020).…”
Section: Methodsmentioning
confidence: 99%